P09 The association of weight gain during adulthood with prostate cancer incidence and survival: the Nord-Trøndelag Health Study-2 cohort, Norway. (16th November 2010) - Chamberlain, C; Romundstad, P; Vatten, L; Gunnell, D; Martin, R M
Abstract : Obese men appear to have an increased risk of being diagnosed with advanced prostate cancer and of dying from the disease. Few studies have examined the impact of weight gain during adulthood on prostate cancer risk and mortality. We analysed data from 20 991 Norwegian men who participated in two phases of the Nord-Trøndelag Health Study in 1984/1986 (HUNT-1, when aged at least 20 years) and 1995/1997 (HUNT-2). Weight and height were measured at both HUNT-1 and HUNT-2, allowing each man's change in weight and BMI during approximately 11 years of adult life to be computed. During a median of 11.3 years of follow-up after the end of HUNT-2, 649 (3%) men developed prostate cancer. We observed an increase in prostate cancer incidence amongst men who put on weight between HUNT-1 and HUNT-2. In multivariable models, including adjustment for weight at HUNT-2, the HR for prostate cancer per one SD (6.2 kg) gain in weight was 1.16 (95% CI 1.03 to to 1.31, p-trend=0.01) and per one SD gain in BMI (1.9 kg/m 2 ) was 1.14 (95% CI 1.00 to 1.30, p-trend=0.04). Amongst men diagnosed with prostate cancer (any stage), there was no evidence that gain in weight prior to diagnosis was positively associated with subsequent all-cause mortality (HR per one SD increase in weight=1.05; 95% CI 0.87 to 1.26, p-trend=0.63). The findings suggest that control of weight gain during adulthood, as well as absolute weight, has implications for prostate carcinogenesis.